Investigation on a low ozone episode at the end of November 2000 and its effect on ultraviolet radiation - SIANI, Anna Maria; CASALE, Giuseppe Rocco; A. Galliani (Optical Engineering, 2002)
At mid-latitudes, ozone variations are mainly caused by horizontal and vertical air transport, while the intensity of sources and sinks play a minor role. A short-lived episode of low ozone values over central Europe on 29 November 2000 was observed at some Italian Brewer stations. The total ozone was reduced by an episodic intrusion of tropical air having an ozone column substantially lower than normal. This reduction was not caused by photochemical reactions, which are responsible for the ozone reduction over Antarctic regions. The investigation was based on the 03 tendency equations for determining the dynamic cause of the low ozone event. Ultraviolet (UV) irradiances variations were also analyzed to determine how weather patterns may lead to enhanced levels of UV radiation within a few days, which, however, was not found to be biologically harmful. (C) 2002 Society of Photo-Optical Instrumentation Engineers.